Riba and Business in Islam - Haq, Furqonul (Jurnal Ar-Ribh, 2022)
This study aims to discuss the relationship between usury and business in Islam. The discussion begins with discussing the meaning of usury, the practice of usury in life, the links and opinions between usury and business in Islam. This research is a qualitative research that emphasizes literature review. The results of the study concluded that all types of usury are unlawful, whether in small or large amounts. Riba is bad for all aspects of life. Riba consists of usury nasiah and usury fadl. The practice of usury in life can occur in public life, banking, the world economy, and can apply to all business sectors. Riba is a disease in the business sector. Riba is the biggest enemy that must be eliminated in Islamic business, because usury is the culprit in Islamic business